University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 4 - Section 4.2 - The Mean Value Theorem - Exercises - Page 223: 34


a) $y=x^2+C$ b) $y=x^2-x+C$ c) $y=x^3+x^2-x+C$

Work Step by Step

a) When $2x=(x^2)'$ Thus, $y'=2x \implies y=x^2+C$ b) When $2x-1=(x^2-x)'$ Thus, $y'=2x-1 \implies y=x^2-x+C$ c) When $3x^2+2x-1=(x^3+x^2-x)'$ Thus, $y'=x^2+x-x \implies y=x^3+x^2-x+C$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.